Equal Current Sharing Parallelly Connected Interleaved Boost Converter in DC Microgrid using Control Algorithm - Vismaya, S.; Hema, S. (Journal of Electronics and Informatics, 2022)
In this paper, a micro grid based current sharing between parallelly connected second order Boost Converter and Interleaved Boost Converter is proposed. As the output of PV is not predictable, an MPPT based on the Adaptive Neuro Fuzzy Inference System (ANFIS) is used to manage the second order Boost Converter. To offer exact sharing of current between parallel modules in converters, a droop control mechanism is utilized. The PV system’s maximum power is tracked using a PI controller, so as to maintain constant DC link voltage at different temperature conditions. Using a PI assisted Bidirectional battery converter, the voltage of the battery is maintained. The nominal voltage for each converter is modified by comparing each converter’s output current to the total load current. The entire system is validated through a MATLAB simulation.
Keywords: Interleaved boost converter; second order boost converter